Glycemic variability indices determined by self-monitoring of blood glucose are associated with β-cell function in Chinese patients with type 2 diabetes. (June 2020) - Zhang, Yusheng; Dai, Jiao; Han, Xiao; Zhao, Yue; Zhang, Hui; Liu, Xuan; Li, Wei; Ling, Hongwei; Zhou, Xiaoyan; Ying, Changjiang
Highlights: SMBG parameters are associated with β-cell function in Chinese T2DM patients SMBG parameters are associated with β-cell function, independent of HbA1c. We conducted the research in patients with a variety of hypoglycemic treatment. Abstract: Introduction: Glycemic control plays an important role in diabetes management, and self-monitoring of blood glucose (SMBG) is critical to achieving good glycemic control. However, there are few studies about the relationship between SMBG-estimated glycemic indices and β-cell function. Here we investigated the association between glucose variation indices estimated by SMBG and β-cell function among Chinese patients with type 2 diabetes mellitus (T2DM). Methods: In this cross‑sectional study, 397 patients with T2DM were recruited from February 2015 to October 2016. β-cell function was monitored using the Homeostasis Model Assessment 2 (HOMA2)-%β index. The parameters evaluated by SMBG were the mean blood glucose (MBG), standard deviation of MBG (SDBG), largest amplitude of glycemic excursions (LAGE), and postprandial glucose excursion (PPGE). Results: HOMA2-%β was negatively correlated with SDBG, LAGE, PPGE, and MBG (r = −0.350, −0.346, −0.178, and −0.631, respectively; all p  < 0.01). After adjusting for confounding characteristics (diabetic duration, triglyceride, total cholesterol, fasting C-peptide, HOMA2-insulin resistance index, hypoglycemia, and diabetic treatments) and glycated hemoglobin A1c on a continuous scale, odds ratios of SDBG, LAGE, PPGE, and MBG between the patients in the lowest and highest HOMA2-%β quartiles were 2.02 (1.14–3.57), 1.24 (1.04–1.49), 1.13 (0.86–1.51), and 2.26 (1.70–3.00). HOMA2-%β was independently associated with SDBG, LAGE, and MBG. Conclusions: Increased SDBG and LAGE assessed by SMBG are associated with β-cell dysfunction in Chinese patients with T2DM.